Neuroprotective Properties of Kempferol Derivatives from Maesa membranacea against Oxidative Stress-Induced Cell Damage: An Association with Cathepsin D Inhibition and PI3K/Akt Activation - Jantas, Danuta; Malarz, Janusz; Le, Thanh Nguyen; Stojakowska, Anna (International journal of molecular sciences, 2021)
As components of the human diet with potential health benefits, flavonols are the subject of numerous studies, confirming their antioxidant, free radical scavenging and anti-inflammatory activity. Taking into consideration the postulated pathogenesis of certain CNS dysfunctions characterized by neuronal degradation, flavonols may prevent the decay of neurons in multiple pathways. Leaves of Maesa membranacea yielded several flavonol glycosides including α-rhamnoisorobin (kaempferol 7-O-α-rhamnoside) and kaempferitrin (kaempferol 3,7-di-O-α-rhamnoside). The latter compound was a major constituent of the investigated plant material. Neuroprotective effects of kaempferitrin and α-rhamnoisorobin were tested in vitro using H2O2-, 6-OHDA- and doxorubicin-induced models of SH-SY5Y cell damage. Both undifferentiated and differentiated neuroblastoma cells were used in the experiments. α-Rhamnoisorobin at a concentration range of 1–10 µM demonstrated cytoprotective effects against H2O2-induced cell damage. The compound (at 1–10 µM) was also effective in attenuating 6-OHDA-induced neurotoxicity. In both H2O2- and 6-OHDA-induced cell damage, kaempferitrin, similar to isoquercitrin, demonstrated neuroprotective activity at the highest of the tested concentrations (50 µM). The tested flavonols were not effective in counteracting doxorubicin-induced cytotoxicity. Their caspase-3- and cathepsin D-inhibitory activities appeared to be structure dependent. Inhibition of the PI3-K/Akt pathway abolished the neuroprotective effect of the investigated flavonols.